Two new flea beetle genera: Alasia alpina gen. et sp. nov. from a Costa Rican cloud forest and Pseudostenophyma gen. nov. from Brazil (Coleoptera: Chrysomelidae: Alticinae) - Furth, David G.; Zhaurova, Kira M. (Zootaxa, 2010)
Alasia alpina is described as a new genus and species from high altitude cloud forests in Heredia, Costa Rica. Morphologically it is distinctive by its overall smooth shiny surface, dark-brown to black coloration, elongate body form; very long antennae, long, slender femora, broadly triangular, subconcave frons with shagreened surface, elytra weakly striate, and structure of the genitalia and metafemoral spring. It apparently prefers Melastomataceae host plants in the forest understory. It is most similar to Pseudostenophyma modesta com. nov. from which it differs in morphology, color, size, altitude of occurrence, and habitat. Stenophyma elegans Baly (type species) was discovered not to be congeneric with the other species in that genus S. modesta Weise, resulting in Pseudostenophyma being established as a new generic name for this taxon (P. modesta).